RECOGNITION OF THE POLITICAL RIGHTS OF ETHNIC MINORITIES IN EUROPEAN COUNTRIES - I. Igonin, Denis; F. Garipov, Ruslan (Gênero & Direito, 2019)
This paper discusses the features of the political rights of ethnic minorities in individual European states. The relevance of the study is due to the fact that this institution is undergoing its transformation. In connection with this fact, object of research in the paper is the analysis of individual international and constitutional acts. The emphasis on ethnic minorities in revealing the essence of political rights is by no means accidental. Legislative registration as a state recognition of the rights of ethnic minorities is a prerequisite for combating discrimination and, at the same time, protecting small groups of people. Therefore, the policy in the field of these rights is a socially significant reality recognized today by the international community. It is the result of ethnosocial consensus. The assertion that the political rights of ethnic minorities are universally recognized is often accompanied by arguments based on modern international norms. But when referring to the main international acts, this issue does not look as clear as it is presented in a number of scientific studies. It does not at all follow from these international acts that these rights belong only to ethnic groups. The term “people” is interpreted as a community of citizens residing both in independent states and in dependent territories. Thus, it is not entirely clear whether a particular European state is obliged to exercise these rights in relation to a single ethnic group, since these international documents do not directly contain such an obligation.